New species of gall wasps (Hymenoptera: Cynipidae: Aulacideini and Phanacidini) inducing galls on plants of the genera Sonchus and Crepis (Asteraceae) in Romania (Dobrogea Province) and notes on their parasitoids - Şchiopu, Ion; Tataroǧlu, Musa; Katilmiş, Yusuf (Zootaxa, 2024)
Two new species of herb gall wasps (Hym., Cynipidae) developing on plants in the genera Sonchus L. and Crepis L. (Asteraceae) are described from Southeastern Romania (Dobrogea Province): Aulacidea andriescui sp. n. gall inducer on Sonchus palustris L. and Phanacis dobrogicus sp. n. gall maker on Crepis foetida subsp. rhoeadifolia (M. Bieb.) Čelak. In addition to the diagnosis, identification, morphological description, life-cycle, geographical distribution, photos of gall and host plant, and SEM images, data on the associated fauna obtained from the galls of the two new species are also presented.